2000
DOI: 10.1038/sj.bmt.1702201
|View full text |Cite
|
Sign up to set email alerts
|

Scoring system for the prediction of successful peripheral blood stem cell (PBSC) collection in non-Hodgkin's lymphoma (NHL): application in clinical practice

Abstract: Summary:Fifty-six patients with chemosensitive NHL were studied to assess factors affecting mobilization and peripheral blood stem cell (PBSC) collection: all were mobilized with high-dose cyclophosphamide and etoposide and G-CSF 5 g/kg/day. None of them had bone marrow involvement at the time of mobilization or a history of extended field irradiation. Previous chemotherapy regimens were divided into two groups: moderately myelotoxic chemotherapy (MMC) and highly myelotoxic chemotherapy (HMC). The adequacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…Overall, the patients were characterized by features that are known to affect standard stem cell mobilization negatively, including advanced age, a diagnosis of NHL, previous radiotherapy, extensive treatment with chemotherapy, treatment with lenalidomide or purine analogues, previous autoSCT, or failure of at least one previous attempt at mobilization [7][8][9][10][11][12][13][14][15]. We observed that, despite these unfavorable characteristics, mobilization with plerixafor and G-CSF enabled the required number of stem cells to be collected in 67.5% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the patients were characterized by features that are known to affect standard stem cell mobilization negatively, including advanced age, a diagnosis of NHL, previous radiotherapy, extensive treatment with chemotherapy, treatment with lenalidomide or purine analogues, previous autoSCT, or failure of at least one previous attempt at mobilization [7][8][9][10][11][12][13][14][15]. We observed that, despite these unfavorable characteristics, mobilization with plerixafor and G-CSF enabled the required number of stem cells to be collected in 67.5% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,[16][17][18] Most studies have included patients with heterogeneous diagnoses, previous therapy and mobilisation regimens. Drake et al 4 proposed a scoring system for previous chemotherapy predicting mobilisation efficiency in a patient population consisting mostly of NHL, Hodgkin's lymphoma and multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other reports, the cumulative myelotoxicity of the drugs previously administered to patients over their disease course seemed to play a role in jeopardizing the yield after mobilization. [18][19][20] According to the phase of the disease, patients with ANLL in CR1, who are less heavily treated, were 'better mobilizers', as compared to patients with ALL in CR2, while patients with ALL in CR3 did not mobilize at all. Moreover, the longer the treatment phase before mobilization, the lower the yield for ANLL patients in CR1.…”
Section: Discussionmentioning
confidence: 99%